Cytotoxic Effects Of Selective Inhibitor 'Aurora Kinase B' On Viability And Metabolic Features Of Human Promyelocytic Leukemia Cell Line - Samad Ghanizadeh Vesali; Farhad Zaker; Ali Zekri; Ardeshir Ghavamzadeh; Kamran Alimoghaddam; Seyed Hamidollah Ghaffari (Tehran University of Medical Sciences, 2013)
Background and Aim: A goal of modern cancer research is to reach targeted therapies with drugs having fewer side effects. AZD1152 is a highly specific inhibitor of Aurora Kinase B, which leads to the programmed cell death by different mechanisms. The aim of this study was to evaluate the effects of AZD1152 on viability and metabolic activity of NB4 cells (APL derived cell line).  Materials and Methods: The cells were treated with various concentrations of AZD1152. After 24, 48 and 72h treatments, the metabolic activity and viability of inhibitor-treated NB4 cells were assessed using MTT and trypan blue dye exclusion assays, respectively. Data were analyzed by applying student's t-test (Microsoft Excel).  Results: A t 25, 50 and 100 nM, AZD1152 reduced the metabolic activity by 9.2, 15.5 and 56.2% (after 24h), 10.3, 19.5 and 59.9% (after 48h), and 17.1, 28.4 and 64.8% (after 72h), respectively. Meanwhile, the percentage of viability was decreased to about 51, 45 and 40% (after 24h), 39, 36 and 30% (after 48h), and 34, 32 and 28% (after 72h), respectively.  Conclusion : According to the results, AZD1152 has substantial efficacy on APL cell line and may be applied in some cases, e. g., for patients who have relapse or who become refractory to the conventional chemotherapy. Further studies are needed to show the molecular mechanisms regulating effects of this anti-cancer agent.